Analisis Biaya Manfaat Pemanfaatan Limbah Sekam Padi dalam Proyek Sosial Lahan Basah untuk Penguatan Ekonomi Desa Sungai Pitung - Aimanullah, Aimanullah; Yuliastina, Mellani; Limarjani, Sustinah; Norlena, Norlena; Amalia, Wia Rizqi; Ansyah, Pathur Razi (Universitas Pahlawan Tuanku Tambusai, 2026)
Sungai Pitung Village, Barito Kuala Regency, is classified as a developed village based on the Village Development Index, yet empirically faces structural problems. Economic dependence on tidal rice monoculture, rice husk waste openly burned, and underutilized vacant land are the main issues. The social project of the Jerami Peduli Team employed a Participatory Rural Appraisal approach with two main interventions: processing rice husk waste into liquid smoke using pyrolysis technology, and cultivating loofah on vacant land. Cost-benefit analysis shows the program is economically feasible with positive net benefits. Beyond financial benefits, the program enhances community capacity, environmental awareness, and creates sustainable productive village assets. This project offers an adaptive and applicable model for wetland-based village empowerment.